Effects of a self‐guided, web‐based activity programme for patients with persistent musculoskeletal pain in primary healthcare: A randomized controlled trial. (2nd May 2017) - Calner, T.; Nordin, C.; Eriksson, M.K.; Nyberg, L.; Gard, G.; Michaelson, P.
Abstract: Background: Web‐based interventions for pain management are increasingly used with possible benefits, but never used in addition to multimodal rehabilitation (MMR). MMR is recommended treatment for persistent pain in Sweden. The aim was to evaluate the effects of a self‐guided, web‐based programme added to MMR for work ability, pain, disability and health‐related quality of life. Methods: We included 99 participants with persistent musculoskeletal pain in a randomized study with two intervention arms: (1) MMR and web‐based intervention, and (2) MMR. Data was collected at baseline, 4 and 12 months. Outcome measures were work ability, working percentage, average pain intensity, pain‐related disability, and health‐related quality of life. Results: There were no significant effects of adding the web‐based intervention to MMR regarding any of the outcome variables. Conclusions: This trial provides no support for adding a self‐guided, web‐based activity programme to MMR for patients with persistent musculoskeletal pain. Significance: The comprehensive self‐guided, web‐based programme for activity, Web‐BCPA, added to multimodal treatment in primary health care had no effect on work ability, pain, disability or health‐related quality of life. Future web‐based interventions should be tailored to patients' individual needs and expectations.